The Will and the Presence of Human Being in Abu al-Hasan al-Ash’ari’s Thought: Explaining the Relation between Human and God in Kalam Discourse - Mohammad Yunus Masrukhin (Al-Jami'ah: Journal of Islamic Studies, 2021)
This article tries to problematize the mainstream academic perspectives about fatalistic orientation and predetermined will of mankind attributed to the thoughts of Abu al-Hasan al-Asy’ari, founder of theological school in Islam named after his name. Benefited from phenomenological approach it proves that Ash’ari has conceptualized that mankind is free creature represented by his/her will as it is related to the will of God. This article argues that Ash’ari’s assertion that humankind has freedom is based on the fact that he/she has ability to feel the presence of the will in his/her consciousness as something belongs to him/her. Departing from the logic of Arabic linguistics, freedom is defined as free will found in human being regardless of whether it is created by mankind or by God. Knowing that human will is created by God theologically doesn’t mean that the will is predetermined in the state of consciousness due to the fact that al-Qur’an states that God has created a feeling of freedom for human being to feel free not to feel being determined. Since the conception of being is elucidated linguistically by Ash’ari as being found by finder, this projection has firmly been compatible with projection of phenomenological consciousness. This article ends with conclusion that the feeling of will in the sense of consciousness of it manifests human freedom without neglecting the will of God. This relation of two wills has enabled human being to be aware of his/her freedom and God’s one as unseparated dualism in human religious experience. [Artikel ini mencoba untuk melakukan problematisasi atas pandangan para sarjana mainsntream dalam diskursus teologi yang menyatakan bahwa pemikiran Abu al-Hasan al-Asy’ari, pendiri mazhab Asy’ariah, adalah fatalistik. Lebih lanjut, artikel ini ingin membuktikan bahwa pemikiran Asy’ari mempunyai perhatian yang besar terhadap kebebasan manusia yang direpresentasikan oleh adanya kehendak manusia yang berelasi dengan kehendak Tuhan dengan pendekatan fenomenologis. Artikel ini menjelaskan bahwa Asy’ari menegaskan kebebasan manusia dengan argumentasi bahwa ia mempunyai kehendak yang hadir dalam kesadarannya dan dinisbatkan kepadanya; orang yang berkehendak adalah orang yang mempunyai kehendak tanpa melihat siapa yang mewujudkan kehendak tersebut. Meskipun Tuhan menciptakan kehendak untuk manusia, tapi secara sadar kehendak itu dinisbatkan manusia. Pandangan Asy’ari tentang kehendak dan kebebasan manusia didasarkan pada logika Bahasa Arab dengan menyatakan bahwa eksistensi adalah wujud yang ditemu oleh manusia yang menemukan, mempunyai kesesuaian dengan fenomenologi yang menyatakan bahwa eksistensi adalah relasi kesadaran manusia terhadap wujud. Dalam konteks ini, kehendak merupakan bukti yang paling kuat atas eksistensi manusia yang bebas. Artikel ini berkesimpulan bahwa dalam pandangan Asy’ari manusia adalah makhluk yang bebas melalui kehendaknya tanpa harus mengkorbankan kehendak Tuhan. Lebih lanjut kehendak manusia dan Tuhan merupakan dualisme kesadaran eksistensialisme yang tak bisa dipisahkan dalam pengalaman kemanusiaan religius.]